Policy Brief 13: Catalysing the private sector for disaster response and resilience – Case study of the Philippine Disaster Resilience Foundation - Hans, Vanessa; Luz, Bill (Basel Institute on Governance Policy Briefs, 2024)
Extreme weather events, earthquakes, volcanic eruptions and epidemics cause the loss of countless lives and bring disruption to many countries. Governments and humanitarian aid agencies are expected to be at the forefront of preparing for and responding to such disasters. However, occasionally the scale and impact of some natural disasters are so large that additional resources beyond what governments can provide become necessary. In such cases, efforts may be perceived as insufficient and slow. Resources and efforts need to be augmented in order to provide relief and support to those who need it most. Could the private sector take a more leading role in pre- and post-disaster efforts? How could a structured, long-term engagement reduce the inevitable integrity risks in high-stress disaster situations involving numerous government, business and international actors? This Policy Brief looks at how the Philippines Disaster Resilience Foundation (PDRF) has emerged as a leading private-sector coordinator for disaster risk reduction and management. It illustrates the important role that the private sector can play in responding to – and building resilience to – natural disasters and other humanitarian emergencies. It also showcases how vital it is for good governance, integrity and transparent collaboration to be at the heart of those efforts.